Respuesta :
Answer:
The inverse is ±sqrt(100-x)
Step-by-step explanation:
y= 100 - x^2
Exchange x and y
x = 100 -y^2
Solve for y
Subtract 100 from each side
x-100 = 100-100-y^2
x-100 = - y^2
Multiply by -1
-x+100 = y^2
100 -x = y^2
Take the square root of each side
±sqrt(100-x) = sqrt(y^2)
±sqrt(100-x) = y
The inverse is ±sqrt(100-x)
Answer:
y = ±√(100 - x)
Step-by-step explanation:
Given: y= 100 - x²
To find the inverse, we have to rearrange the equation such that we express x in terms of y.
y= 100 - x² (add x² to both sides)
y + x² = 100 (subtract y from both sides)
x² = 100 - y
x = ±√(100 - y) (final step: swap x and y terms)
y = ±√(100 - x) (answer)